COVID-19 infection presented as Guillain-Barre Syndrome: Report of two new cases and review of 116 reported cases and case series - Abdel-Naser Elzouki (9376853) (2021)
Aims Corona virus disease 2019 (COVID 19) is a pandemic infectious disease of 2020, which often presents with respiratory and gastrointestinal symptoms. The behavior of the virus and its full clinical picture has not been fully studied yet. Many case reports and case series have been running in order to elaborate different presentations and associations. Pulmonary and gastrointestinal features of COVID-19 infection are well outlined; however, neurological manifestations are less defined. Case presentation We report two adult cases of COVID-19 infection presented with acute Guillain-Barre Syndrome (GBS), and a literature review on the causal association between COVID-19 and GBS. Conclusion Our two case reports in addition to literature review of 116 published cases may help offer insight into the clinical course of COVID-19 infection. Our two COVID-19 patients presented with neurological manifestations of GBS which were not preceded with any respiratory, gastrointestinal or other systemic infection. This leads us to raise the possibility of establish direct causal association between COVID-19 infection and GBS. Physicians should have high clinical suspicions when encounter GBS patient during the current COVID-19 pandemic and consider co-existence of COVID-19 infection that may warrant SARS-CoV-2 testing, isolation precautions, and specific treatment for Covid-19 infection. Other Information Published in: Travel Medicine and Infectious Disease License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.tmaid.2021.102169